Critical analysis of palliative surgical therapy for advanced thoracic esophageal cancer - de Aquino, Jose Luis Braga; Leandro Merhi, Vania Aparecida (Seven Editora, 2023)
Although malignant neoplasm of the esophagus is a disease with a high incidence, its diagnosis is often still delayed. This fact combined with excessive weight loss due to dysphagia and the association with car-diopulmonary diseases resulting from excessive tobacco use, makes these patients have a difficult clinical control, which explains that more than 50% of them require palliative treatment. The ideal scenario would be to perform procedures that provide an adequate quality of life and with satisfactory rescue of swallowing, without the need for frequent hospitalizations and with a low rate of complications. Thus, this chapter aims to discredit the indications and results of palliative methods and especially shunt surgeries, discussing the technique of isoperistaltic gastric tube of great healing (GIT). In the Department of Surgery of Hospital PUC Campinas, 143 patients with unresectable esophageal squamous cell carcinoma (T4b) were studied, and all of them had clinical conditions to be submitted to GIT. In the early postoperative evaluation, 64p (44.7%) presented systemic complications, with pulmonary infection being the most frequent; 51p (35.6%) presented local complications, with dehiscence of the cervical esophagogastric anastomosis being the most frequent. 13p (9.1%) died due to postoperative complications. Of the 112 patients who were properly followed, 91 (81.2%) presented good palliation with this procedure, with adequate swallowing rescue. Chemoradiation was performed after the TGI in 82 patients, with a mean survival of 3 years in 63 patients (76.8%). With these results, it is possible to conclude that despite the postoperative morbidity not being negligible, the TGI can be performed safely, especially after the advent of mechanical suture, because it offers adequate palliation and survival. In addition, this procedure has the advantage of simultaneously providing good drainage of the esophagus and stomach, and thus potentially avoiding esophageal mucocele.DOI:https://doi.org/10.56238/globalhealthprespesc-078